Synthesis and antimicrobial evaluation of novel 1,2,4-triazole derivatives - Panasenko, O. I.; Панасенко, О. І.; Panasenko, M. O.; Панасенко, М. О.; Zazharskiy, Vladymyr; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Volodymyr V.; Zazharskiy, V. V.; et al. (Oles Honchar Dnipropetrovsk National University, 2025)
Derivatives of 1,2,4-triazole are widely recognized as promising scaffolds for the development of biologically a c tive compounds, particularly those exhibiting antimicrobial properties. In the present study, the antimicrobial potential of a series of newly synthesized 1,2,4-triazole-based heterocyclic compounds was investigated using the in vitro disk diffusion method against 15 clinically significant bacterial strains, including both Gram-positive and Gram-negative species. The compounds were dissolved in 70% ethanol and tested at different concentrations to assess their spectrum and degree of antibacterial activity. One compound, ethyl 2-((3-mercapto-9-methylpyrazolo[1,5-d][1,2,4]triazolo[3,4-f][1,2,4]triazin-6-yl)thio)acetate, exhibited the most pronounced inhibitory effect, producing zones of bacterial growth inhibition exceeding 8 mm in diameter in 14 out of the 15 tested bacterial strains. Several other derivatives, particula r ly those bearing N-ethyl or N-phenyl substitutions within triazolothiadiazole frameworks, as well as dichlorophenyl-substituted triazolothiadiazines, exhibited moderate antibacterial activity, inhibiting the growth of five to seven ba c terial strains depending on their structural features. The structure – activity relationship analysis suggests that the pre s ence of electron-withdrawing groups, fused heterocyclic systems and s ulfur-containing linkages may contribute to enhanced biological activity. Overall, the results underscore the importance of the 1,2,4-triazole core in the design of novel antimicrobial agents and provide a solid foundation for further structural optimization and pharmaceutical d e velopment of these compounds. Похідні 1,2,4-тріазолу широко визнані як перспективні основи для розробки біологічно активних сполук, зокрема тих, що проявляють антимікробні властивості. У цьому дослідженні антимікробний потенціал серії нещодавно синтезованих гетероциклічних сполук на основі 1,2,4-тріазолу було досліджено за допомогою методу дискової дифузії in vitro проти 15 клінічно значущих бактеріальних штамів, включаючи як грампозитивні, так і грамнегативні види. Сполуки розчиняли у 70% етанолі та тестували при різних концентраціях для оцінки їх спектру та ступеня антибактеріальної активності. Одна сполука, етил 2-((3-меркапто-9-метилпіразоло[1,5-d][1,2,4]тріазоло[3,4-f][1,2,4]тріазин-6-іл)тіо)ацетат, продемонструвала найбільш виражений інгібуючий ефект, утворюючи зони пригнічення росту бактерій діаметром понад 8 мм у 14 з 15 протестованих бактеріальних штамів. Кілька інших похідних, зокрема ті, що містять N-етилові або N-фенільні заміщення в триазолотіадіазольних каркасах, а також дихлорфенілзаміщені триазолотіадіазини, продемонстрували помірну антибактеріальну активність, пригнічуючи ріст від п'яти до семи штамів бактерій залежно від їхніх структурних особливостей. Аналіз взаємозв'язку структура-активність свідчить про те, що наявність електроноакцепторних груп, конденсованих гетероциклічних систем та сірковмісних зв'язків може сприяти посиленню біологічної активності. Загалом, результати підкреслюють важливість 1,2,4-триазольного ядра в розробці нових антимікробних засобів та забезпечують міцну основу для подальшої структурної оптимізації та фармацевтичної розробки цих сполук.
Синтез та антимікробна оцінка нових похідних 1,2,4-тріазолу
Зажарський Володимир Володимирович https://orcid.org/0000-0003-2674-2494 Зажарська Надія Миколаївна https://orcid.org/0000-0002-8328-6440
Keywords: multidrug-resistant strain; штам з множинною лікарською стійкістю; properties; властивості; growth inhibition zone; зона затримки росту; bacterial colonies; бактеріальні колонії